Anti-windup disturbance feedback control: Practical design with robustness. (September 2018) - Kawai, Fukiko; Vinther, Kasper; Andersen, Palle; Bendtsen, Jan Dimon
Highlights: A design method of robust disturbance feedback control (DFC) is proposed. The robust DFC is designed by a linear matrix inequality (LMI) approach. The proposed method is applied to industrial refrigeration systems. The results indicate that both robustness and performance can be improved. Abstract: This paper presents a practical design method of robust disturbance feedback control (DFC) along with an application to industrial refrigeration systems. DFC is a controller configuration in which an existing controller is augmented with an additional loop. The design method for DFC is proposed in two steps; firstly, the robust DFC without saturation is designed by a linear matrix inequality (LMI) approach, and then LMI techniques are used again for designing an anti-windup compensator to accommodate actuator saturation. The proposed method is compared to a conventional design on a water chiller system, both in simulation and through practical experiments. The test results indicate that both robustness and performance can be improved in the presence of model uncertainties, and the proposed method can avoid wind-up phenomena when the control inputs are saturated.